Досвід використання рисполепту-конста в лікуванні ендогенних психозів - Зільберблат, Г.М.; Тімен, М.Є.; Єршова, О.А.; Іващенко, Н.Є.; Січкар, І.В. (Фізико-хімічний інститут ім. О.В.Богатського НАН України, 2008)
Исследована эффективность и переносимость первого антипсихотика-пролонга у 46 пациентов с эндогенными психозами. Рисполепт-конста хорошо переносился пациентами, уменьшал психотическую симптоматику, улучшал социальное функционирование, значительно снижал частоту госпитализации. В исследовании обнаружено существенное позитивное влияние рисполепта-конста на коморбидную аддиктивную патологию и шизотипическое расстройство. The efficiency of use and safety of the first long-acting atypical antipsychotic have been studied in 46 patients with endogenous psychosis. Long-acting risperidone good stand by patients, reduced psychotic symptoms, improved social functioning, markedly decreased frequency of hospitalization. Research has revealed considerable positive action of long-acting risperidone in treatment of schizotypical disorders and comorbid addictive pathology.